Integrating Nutrition Education and Entrepreneurship Development In Nagubi (Cassava Leaf Nuggets) Product Development: A Multidisciplinary Collaboration Model for Empowering Coastal Communities in Boneatiro Barat District, Buton Regency, Indonesia - Dwi Agustyawati; Rusman Raml; Wa Ode Sriwati Lestari; Nur Zarliani Uli; Hasni; Masduki Mahfud; Novika Anggraini (Jurnal Pengabdian Masyarakat Sabangka, 2026)
This community service program aimed to develop NAGUBI (Cassava Leaf Nuggets) by integrating nutrition education and entrepreneurship strengthening as a community empowerment model for coastal communities. The program employed a participatory approach involving lecturers from the fields of health and management. The activities included community needs assessment, nutrition education, NAGUBI production training, product packaging, marketing, business mentoring, and program evaluation. Data were collected through observation, documentation, discussions, and field notes, and were analyzed using a descriptive qualitative approach. The results demonstrated improved participants’ understanding of the nutritional value of cassava leaves, enhanced skills in producing NAGUBI, and strengthened basic business management competencies. The program contributed to increasing the added value of local food resources, promoting community economic self-reliance, and strengthening the sustainable economic potential of coastal communities through innovation based on local resources.